Neck sweat gland cancer hemorrhage. Case study - Ciesielski, Przemysław; Górnicka, Barbara; Górnicki, Krzysztof; Kołodziejczak, Malgorzata; Siekierski, Paweł (Contemporary Oncology/Współczesna Onkologia, 2013)
Background: This paper reports a case of an 87-year-old female patient who was admitted for an emergency operation due to massive hemorrhage of an ulceration localized on a huge neck tumor. Post-interventional diagnosis indicated hidradenocarcinoma. Hidradenocarcinoma is a rare skin neoplasm. It can coincide with adenoma, may develop through its malignant transformation or develop as a malignant tumor from the beginning. It may be found in all dermal localizations. It may develop metastases or appear in the diffuse form. Material and methods : Surgical excision of the tumor was performed obtaining a surgical margin, completed with excision of local lymph nodes and multiple layer suturing. Due to lack of the patient’s consent, she has not been qualified for adjuvant therapy. Results : Control examination 6 and 12 months later showed no signs of local recurrence or lymph node metastasis. Conclusion: Surgical excision of apocrine hidradenocarcinoma with a surgical margin could present a good therapeutic effect in spite of lack of adjuvant therapy.